Features mode of pupils bay, methods of its correction by means of physical culture - Істомін [Istomin Andrej] Андрій Георгійович; Лукавенко [Lukavenko Olena] Олена Геннадіївна; Ленська [Lenska Olga] Ольга В’ячеславівна; Лобaньова [Lobanyva Olga] Ольга Володимирівна; Тимбота [Tymbota Miroclav] Мирослав Олексійович (Slobozhanskyi Herald of Science and Sport, 2013)
The science and research work is devoted to actual problem of juvenile health. The mode of the day peculiarities for teenagers of 13–14 years old were researched. The necessary conditions to preserve and strengthen the health of schoolchildren were revealed. Practical recommendations for the mode of the day organization were created in order to improve the health conditions and working capacity